An electric field induced reversible single-molecule fluorescence switch. Issue 34 (31st March 2015) - Wu, Ruixiang; Chen, Ruiyun; Qin, Chengbing; Gao, Yan; Qiao, Zhixing; Zhang, Guofeng; Xiao, Liantuan; Jia, Suotang
Abstract : Based on the intramolecular electron transfer within a single molecule, we have achieved fluorescence switch induced by the electric field. Abstract : We report that by applying an electric field to a single squaraine-derived rotaxane (SR) molecule on bare glass, the fluorescence can be completely quenched. The molecule undergoes a reversible fluorescence switch between a zero-field "on" state and a high-field "off" state, which is attributed to intramolecular electron transfer within the SR molecule.